Dynamic Characteristics of a Double-Pylon Cable-Stayed Bridge with Steel Truss Girder and Single-Cable Plane. (16th December 2021) - Zeng, Yong; Zeng, Yutong; Yu, Hao; Tan, Yujie; Tan, Hongmei; Zheng, Huijun
Abstract : The dynamic characteristics are closely linked to the seismic stability and wind-resistant of the bridge. But different bridge types have different dynamic characteristics. In order to study the dynamic characteristics of a double-pylon cable-stayed bridge with a single-cable plane and steel truss girder whose main span is the longest in the world, the dynamic load test was done, and the finite element and the subspace iteration methods were used to analyze the vibration mode of the bridge. The influence of different structural parameters on the dynamic characteristics of the bridge was analyzed. The changed structural parameters are cable layout, stiffness of steel truss girder, stiffness of stayed cables, stiffness of pylons, the concentration of dead load, number and location of auxiliary piers, and structural system. The results show that the bending and torsion resistance of the double-pylon cable-stayed bridge with a single-cable plane and steel truss girder is weak. The torsional stiffness of the cable-stayed bridge with a double-cable plane is stronger than that of the cable-stayed bridge with a single-cable plane. The seismic stability and wind-resistant of the bridge can be improved by using light dead load, improving the stiffness of pylon and girder, and adding auxiliary piers scientifically. However, the change of cable stiffness has a complex influence on the dynamic characteristics of the bridge. The conclusion can offer references for the construction, maintenance, and design of the same type of bridges.